generating function of numbers of visits up to time n
I want to determine the generating function of the numbers of visits up to a specific time. Formally: let ${X_{n}}_{n geq 0}$ be a markov chain on the state space $S = {1,ldots,r}$ with transition matrix $P = (p_{i,j})_{1 leq i,j leq r}$ and initial probability vector $alpha = (alpha_{i} : i in S)$ with $alpha_{i} = mathbb{P}(X_{0} = i)$. Let $q(n_{1},ldots,n_{r})$ be the probability that up to time $n-1$ the state $1$ is visited $n_{1}$-times,$ldots$,state $r$ is visited $n_{r}$-times and $F_{n}(x_{1},ldots,x_{r}) = sum_{n_{1}+ cdots +n_{r} = n}q(n_{1},ldots,n_{r})x_{1}^{n_{1}}cdots x_{r}^{n_{r}}$ be the corresponding generating function of $q(n_{1},ldots,n_{r})$. Now I want to show that
$$
F_{n}(x_{1},ldots,x_{r}) = (alpha_{1}x_{1},ldots,alpha_{r}x_{r}) left( P D_{r}right)^{n-1} e,
$$
where $e = (1,ldots,1)^{intercal}$ and $D$ is given by
$$
D =
begin{bmatrix}
x_{1} && \
& ddots &\
& & x_{r}
end{bmatrix}.
$$
Here is my solution:
$$
begin{align*}
sum_{n_{1} + cdots + n_{r} = n}q(n_{1},ldots,n_{r}) &= sum_{j in I}mathbb{P}(X_{n-1} = j) \
&= sum_{j in I}sum_{i in I}alpha_{i}p_{i,j}^{n-1} \
&= left(sum_{i in I}alpha_{i}p_{i,1}^{n-1},ldots,sum_{i in I}alpha_{i}p_{i,r}^{n-1} right) e \
&= alpha P^{(n-1)} e.
end{align*}
$$
Does this suffice as a proof and is it correct? Thanks for any help!
probability probability-theory proof-verification markov-chains generating-functions
add a comment |
I want to determine the generating function of the numbers of visits up to a specific time. Formally: let ${X_{n}}_{n geq 0}$ be a markov chain on the state space $S = {1,ldots,r}$ with transition matrix $P = (p_{i,j})_{1 leq i,j leq r}$ and initial probability vector $alpha = (alpha_{i} : i in S)$ with $alpha_{i} = mathbb{P}(X_{0} = i)$. Let $q(n_{1},ldots,n_{r})$ be the probability that up to time $n-1$ the state $1$ is visited $n_{1}$-times,$ldots$,state $r$ is visited $n_{r}$-times and $F_{n}(x_{1},ldots,x_{r}) = sum_{n_{1}+ cdots +n_{r} = n}q(n_{1},ldots,n_{r})x_{1}^{n_{1}}cdots x_{r}^{n_{r}}$ be the corresponding generating function of $q(n_{1},ldots,n_{r})$. Now I want to show that
$$
F_{n}(x_{1},ldots,x_{r}) = (alpha_{1}x_{1},ldots,alpha_{r}x_{r}) left( P D_{r}right)^{n-1} e,
$$
where $e = (1,ldots,1)^{intercal}$ and $D$ is given by
$$
D =
begin{bmatrix}
x_{1} && \
& ddots &\
& & x_{r}
end{bmatrix}.
$$
Here is my solution:
$$
begin{align*}
sum_{n_{1} + cdots + n_{r} = n}q(n_{1},ldots,n_{r}) &= sum_{j in I}mathbb{P}(X_{n-1} = j) \
&= sum_{j in I}sum_{i in I}alpha_{i}p_{i,j}^{n-1} \
&= left(sum_{i in I}alpha_{i}p_{i,1}^{n-1},ldots,sum_{i in I}alpha_{i}p_{i,r}^{n-1} right) e \
&= alpha P^{(n-1)} e.
end{align*}
$$
Does this suffice as a proof and is it correct? Thanks for any help!
probability probability-theory proof-verification markov-chains generating-functions
add a comment |
I want to determine the generating function of the numbers of visits up to a specific time. Formally: let ${X_{n}}_{n geq 0}$ be a markov chain on the state space $S = {1,ldots,r}$ with transition matrix $P = (p_{i,j})_{1 leq i,j leq r}$ and initial probability vector $alpha = (alpha_{i} : i in S)$ with $alpha_{i} = mathbb{P}(X_{0} = i)$. Let $q(n_{1},ldots,n_{r})$ be the probability that up to time $n-1$ the state $1$ is visited $n_{1}$-times,$ldots$,state $r$ is visited $n_{r}$-times and $F_{n}(x_{1},ldots,x_{r}) = sum_{n_{1}+ cdots +n_{r} = n}q(n_{1},ldots,n_{r})x_{1}^{n_{1}}cdots x_{r}^{n_{r}}$ be the corresponding generating function of $q(n_{1},ldots,n_{r})$. Now I want to show that
$$
F_{n}(x_{1},ldots,x_{r}) = (alpha_{1}x_{1},ldots,alpha_{r}x_{r}) left( P D_{r}right)^{n-1} e,
$$
where $e = (1,ldots,1)^{intercal}$ and $D$ is given by
$$
D =
begin{bmatrix}
x_{1} && \
& ddots &\
& & x_{r}
end{bmatrix}.
$$
Here is my solution:
$$
begin{align*}
sum_{n_{1} + cdots + n_{r} = n}q(n_{1},ldots,n_{r}) &= sum_{j in I}mathbb{P}(X_{n-1} = j) \
&= sum_{j in I}sum_{i in I}alpha_{i}p_{i,j}^{n-1} \
&= left(sum_{i in I}alpha_{i}p_{i,1}^{n-1},ldots,sum_{i in I}alpha_{i}p_{i,r}^{n-1} right) e \
&= alpha P^{(n-1)} e.
end{align*}
$$
Does this suffice as a proof and is it correct? Thanks for any help!
probability probability-theory proof-verification markov-chains generating-functions
I want to determine the generating function of the numbers of visits up to a specific time. Formally: let ${X_{n}}_{n geq 0}$ be a markov chain on the state space $S = {1,ldots,r}$ with transition matrix $P = (p_{i,j})_{1 leq i,j leq r}$ and initial probability vector $alpha = (alpha_{i} : i in S)$ with $alpha_{i} = mathbb{P}(X_{0} = i)$. Let $q(n_{1},ldots,n_{r})$ be the probability that up to time $n-1$ the state $1$ is visited $n_{1}$-times,$ldots$,state $r$ is visited $n_{r}$-times and $F_{n}(x_{1},ldots,x_{r}) = sum_{n_{1}+ cdots +n_{r} = n}q(n_{1},ldots,n_{r})x_{1}^{n_{1}}cdots x_{r}^{n_{r}}$ be the corresponding generating function of $q(n_{1},ldots,n_{r})$. Now I want to show that
$$
F_{n}(x_{1},ldots,x_{r}) = (alpha_{1}x_{1},ldots,alpha_{r}x_{r}) left( P D_{r}right)^{n-1} e,
$$
where $e = (1,ldots,1)^{intercal}$ and $D$ is given by
$$
D =
begin{bmatrix}
x_{1} && \
& ddots &\
& & x_{r}
end{bmatrix}.
$$
Here is my solution:
$$
begin{align*}
sum_{n_{1} + cdots + n_{r} = n}q(n_{1},ldots,n_{r}) &= sum_{j in I}mathbb{P}(X_{n-1} = j) \
&= sum_{j in I}sum_{i in I}alpha_{i}p_{i,j}^{n-1} \
&= left(sum_{i in I}alpha_{i}p_{i,1}^{n-1},ldots,sum_{i in I}alpha_{i}p_{i,r}^{n-1} right) e \
&= alpha P^{(n-1)} e.
end{align*}
$$
Does this suffice as a proof and is it correct? Thanks for any help!
probability probability-theory proof-verification markov-chains generating-functions
probability probability-theory proof-verification markov-chains generating-functions
edited Jan 4 at 13:30
Scientifica
6,37641335
6,37641335
asked Jan 4 at 13:17
waynewayne
497113
497113
add a comment |
add a comment |
1 Answer
1
active
oldest
votes
Your computation is correct but it only proves the special case $x_1 = ldots = x_r = 1$.
To prove the general case, set $$A(n_1, ldots, n_r) = left{sigma colon {0, ldots, n-1} to I ; middle| ; #sigma^{-1}(i) = n_iright}.$$
Then $$begin{align*} q(n_1,ldots, n_r) &= mathbb{P}big(exists sigma in A(n_1, ldots, n_r), , X_k = sigma(k) text{ for } 0 leq k leq n-1 big) \ &= sum_{sigma in A(n_1, ldots, n_r)} mathbb{P}big( X_k = sigma(k) text{ for } 0 leq k leq n-1big) \ &= sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)). end{align*}$$
Now we get
$$begin{align*} F_n(x_1, ldots, x_n) &= sum_{n_1 + ldots + n_r = n}q(n_1,ldots, n_r) x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n} bigg(sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) bigg)x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n \ sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} \ &= sum_{sigma in A} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} end{align*}$$
where $A = bigcup_{n_1 + cdots + n_r = n} A(n_1, ldots, n_r)$. The last equality is due to the fact that the $A(n_1, ldots, n_r)$ are pairwise disjoint. Notice that $A$ is actually the set of all functions from ${0, ldots, n-1}$ to $I$. This is because if $sigma$ is such a function, then setting $n_i = # sigma^{-1}(i)$ we have $sum_i n_i = # sigma^{-1}(I) = # {0, ldots, n-1 } = n$ and clearly $sigma in A(n_1, ldots, n_r)$. On the other hand, we have $x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} = x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}$ (by counting the number of times that each of the $x_i$ appears in both terms). Therefore
$$ begin{align*}F_n(x_1, ldots, x_n) = sum_{sigma colon {0, ldots, n-1} to I} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}.end{align*}$$
This can be rewritten as $$F_n(x_1, ldots, x_n) = sum_{i_0, ldots, i_{n-1} in I} alpha_{i_0}x_{i_0}p(i_0,i_1)x_{i_1}cdots p(i_{n-2}, i_{n-1})x_{i_{n-1}}.$$
Finally, if you develop the RHS you get the same expression which proves the desired equality.
add a comment |
Your Answer
StackExchange.ifUsing("editor", function () {
return StackExchange.using("mathjaxEditing", function () {
StackExchange.MarkdownEditor.creationCallbacks.add(function (editor, postfix) {
StackExchange.mathjaxEditing.prepareWmdForMathJax(editor, postfix, [["$", "$"], ["\\(","\\)"]]);
});
});
}, "mathjax-editing");
StackExchange.ready(function() {
var channelOptions = {
tags: "".split(" "),
id: "69"
};
initTagRenderer("".split(" "), "".split(" "), channelOptions);
StackExchange.using("externalEditor", function() {
// Have to fire editor after snippets, if snippets enabled
if (StackExchange.settings.snippets.snippetsEnabled) {
StackExchange.using("snippets", function() {
createEditor();
});
}
else {
createEditor();
}
});
function createEditor() {
StackExchange.prepareEditor({
heartbeatType: 'answer',
autoActivateHeartbeat: false,
convertImagesToLinks: true,
noModals: true,
showLowRepImageUploadWarning: true,
reputationToPostImages: 10,
bindNavPrevention: true,
postfix: "",
imageUploader: {
brandingHtml: "Powered by u003ca class="icon-imgur-white" href="https://imgur.com/"u003eu003c/au003e",
contentPolicyHtml: "User contributions licensed under u003ca href="https://creativecommons.org/licenses/by-sa/3.0/"u003ecc by-sa 3.0 with attribution requiredu003c/au003e u003ca href="https://stackoverflow.com/legal/content-policy"u003e(content policy)u003c/au003e",
allowUrls: true
},
noCode: true, onDemand: true,
discardSelector: ".discard-answer"
,immediatelyShowMarkdownHelp:true
});
}
});
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3061641%2fgenerating-function-of-numbers-of-visits-up-to-time-n%23new-answer', 'question_page');
}
);
Post as a guest
Required, but never shown
1 Answer
1
active
oldest
votes
1 Answer
1
active
oldest
votes
active
oldest
votes
active
oldest
votes
Your computation is correct but it only proves the special case $x_1 = ldots = x_r = 1$.
To prove the general case, set $$A(n_1, ldots, n_r) = left{sigma colon {0, ldots, n-1} to I ; middle| ; #sigma^{-1}(i) = n_iright}.$$
Then $$begin{align*} q(n_1,ldots, n_r) &= mathbb{P}big(exists sigma in A(n_1, ldots, n_r), , X_k = sigma(k) text{ for } 0 leq k leq n-1 big) \ &= sum_{sigma in A(n_1, ldots, n_r)} mathbb{P}big( X_k = sigma(k) text{ for } 0 leq k leq n-1big) \ &= sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)). end{align*}$$
Now we get
$$begin{align*} F_n(x_1, ldots, x_n) &= sum_{n_1 + ldots + n_r = n}q(n_1,ldots, n_r) x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n} bigg(sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) bigg)x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n \ sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} \ &= sum_{sigma in A} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} end{align*}$$
where $A = bigcup_{n_1 + cdots + n_r = n} A(n_1, ldots, n_r)$. The last equality is due to the fact that the $A(n_1, ldots, n_r)$ are pairwise disjoint. Notice that $A$ is actually the set of all functions from ${0, ldots, n-1}$ to $I$. This is because if $sigma$ is such a function, then setting $n_i = # sigma^{-1}(i)$ we have $sum_i n_i = # sigma^{-1}(I) = # {0, ldots, n-1 } = n$ and clearly $sigma in A(n_1, ldots, n_r)$. On the other hand, we have $x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} = x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}$ (by counting the number of times that each of the $x_i$ appears in both terms). Therefore
$$ begin{align*}F_n(x_1, ldots, x_n) = sum_{sigma colon {0, ldots, n-1} to I} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}.end{align*}$$
This can be rewritten as $$F_n(x_1, ldots, x_n) = sum_{i_0, ldots, i_{n-1} in I} alpha_{i_0}x_{i_0}p(i_0,i_1)x_{i_1}cdots p(i_{n-2}, i_{n-1})x_{i_{n-1}}.$$
Finally, if you develop the RHS you get the same expression which proves the desired equality.
add a comment |
Your computation is correct but it only proves the special case $x_1 = ldots = x_r = 1$.
To prove the general case, set $$A(n_1, ldots, n_r) = left{sigma colon {0, ldots, n-1} to I ; middle| ; #sigma^{-1}(i) = n_iright}.$$
Then $$begin{align*} q(n_1,ldots, n_r) &= mathbb{P}big(exists sigma in A(n_1, ldots, n_r), , X_k = sigma(k) text{ for } 0 leq k leq n-1 big) \ &= sum_{sigma in A(n_1, ldots, n_r)} mathbb{P}big( X_k = sigma(k) text{ for } 0 leq k leq n-1big) \ &= sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)). end{align*}$$
Now we get
$$begin{align*} F_n(x_1, ldots, x_n) &= sum_{n_1 + ldots + n_r = n}q(n_1,ldots, n_r) x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n} bigg(sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) bigg)x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n \ sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} \ &= sum_{sigma in A} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} end{align*}$$
where $A = bigcup_{n_1 + cdots + n_r = n} A(n_1, ldots, n_r)$. The last equality is due to the fact that the $A(n_1, ldots, n_r)$ are pairwise disjoint. Notice that $A$ is actually the set of all functions from ${0, ldots, n-1}$ to $I$. This is because if $sigma$ is such a function, then setting $n_i = # sigma^{-1}(i)$ we have $sum_i n_i = # sigma^{-1}(I) = # {0, ldots, n-1 } = n$ and clearly $sigma in A(n_1, ldots, n_r)$. On the other hand, we have $x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} = x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}$ (by counting the number of times that each of the $x_i$ appears in both terms). Therefore
$$ begin{align*}F_n(x_1, ldots, x_n) = sum_{sigma colon {0, ldots, n-1} to I} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}.end{align*}$$
This can be rewritten as $$F_n(x_1, ldots, x_n) = sum_{i_0, ldots, i_{n-1} in I} alpha_{i_0}x_{i_0}p(i_0,i_1)x_{i_1}cdots p(i_{n-2}, i_{n-1})x_{i_{n-1}}.$$
Finally, if you develop the RHS you get the same expression which proves the desired equality.
add a comment |
Your computation is correct but it only proves the special case $x_1 = ldots = x_r = 1$.
To prove the general case, set $$A(n_1, ldots, n_r) = left{sigma colon {0, ldots, n-1} to I ; middle| ; #sigma^{-1}(i) = n_iright}.$$
Then $$begin{align*} q(n_1,ldots, n_r) &= mathbb{P}big(exists sigma in A(n_1, ldots, n_r), , X_k = sigma(k) text{ for } 0 leq k leq n-1 big) \ &= sum_{sigma in A(n_1, ldots, n_r)} mathbb{P}big( X_k = sigma(k) text{ for } 0 leq k leq n-1big) \ &= sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)). end{align*}$$
Now we get
$$begin{align*} F_n(x_1, ldots, x_n) &= sum_{n_1 + ldots + n_r = n}q(n_1,ldots, n_r) x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n} bigg(sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) bigg)x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n \ sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} \ &= sum_{sigma in A} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} end{align*}$$
where $A = bigcup_{n_1 + cdots + n_r = n} A(n_1, ldots, n_r)$. The last equality is due to the fact that the $A(n_1, ldots, n_r)$ are pairwise disjoint. Notice that $A$ is actually the set of all functions from ${0, ldots, n-1}$ to $I$. This is because if $sigma$ is such a function, then setting $n_i = # sigma^{-1}(i)$ we have $sum_i n_i = # sigma^{-1}(I) = # {0, ldots, n-1 } = n$ and clearly $sigma in A(n_1, ldots, n_r)$. On the other hand, we have $x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} = x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}$ (by counting the number of times that each of the $x_i$ appears in both terms). Therefore
$$ begin{align*}F_n(x_1, ldots, x_n) = sum_{sigma colon {0, ldots, n-1} to I} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}.end{align*}$$
This can be rewritten as $$F_n(x_1, ldots, x_n) = sum_{i_0, ldots, i_{n-1} in I} alpha_{i_0}x_{i_0}p(i_0,i_1)x_{i_1}cdots p(i_{n-2}, i_{n-1})x_{i_{n-1}}.$$
Finally, if you develop the RHS you get the same expression which proves the desired equality.
Your computation is correct but it only proves the special case $x_1 = ldots = x_r = 1$.
To prove the general case, set $$A(n_1, ldots, n_r) = left{sigma colon {0, ldots, n-1} to I ; middle| ; #sigma^{-1}(i) = n_iright}.$$
Then $$begin{align*} q(n_1,ldots, n_r) &= mathbb{P}big(exists sigma in A(n_1, ldots, n_r), , X_k = sigma(k) text{ for } 0 leq k leq n-1 big) \ &= sum_{sigma in A(n_1, ldots, n_r)} mathbb{P}big( X_k = sigma(k) text{ for } 0 leq k leq n-1big) \ &= sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)). end{align*}$$
Now we get
$$begin{align*} F_n(x_1, ldots, x_n) &= sum_{n_1 + ldots + n_r = n}q(n_1,ldots, n_r) x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n} bigg(sum_{sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) bigg)x_1^{n_1} cdots x_r^{n_r} \ &= sum_{n_1 + ldots + n_r = n \ sigma in A(n_1, ldots, n_r)} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} \ &= sum_{sigma in A} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} end{align*}$$
where $A = bigcup_{n_1 + cdots + n_r = n} A(n_1, ldots, n_r)$. The last equality is due to the fact that the $A(n_1, ldots, n_r)$ are pairwise disjoint. Notice that $A$ is actually the set of all functions from ${0, ldots, n-1}$ to $I$. This is because if $sigma$ is such a function, then setting $n_i = # sigma^{-1}(i)$ we have $sum_i n_i = # sigma^{-1}(I) = # {0, ldots, n-1 } = n$ and clearly $sigma in A(n_1, ldots, n_r)$. On the other hand, we have $x_1^{#sigma^{-1}(1)} cdots x_r^{#sigma^{-1}(r)} = x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}$ (by counting the number of times that each of the $x_i$ appears in both terms). Therefore
$$ begin{align*}F_n(x_1, ldots, x_n) = sum_{sigma colon {0, ldots, n-1} to I} alpha_{sigma(0)}p(sigma(0),sigma(1))cdots p(sigma(n-2), sigma(n-1)) x_{sigma(0)}x_{sigma(1)} cdots x_{sigma(n-1)}.end{align*}$$
This can be rewritten as $$F_n(x_1, ldots, x_n) = sum_{i_0, ldots, i_{n-1} in I} alpha_{i_0}x_{i_0}p(i_0,i_1)x_{i_1}cdots p(i_{n-2}, i_{n-1})x_{i_{n-1}}.$$
Finally, if you develop the RHS you get the same expression which proves the desired equality.
answered Jan 5 at 22:04
MichhMichh
22316
22316
add a comment |
add a comment |
Thanks for contributing an answer to Mathematics Stack Exchange!
- Please be sure to answer the question. Provide details and share your research!
But avoid …
- Asking for help, clarification, or responding to other answers.
- Making statements based on opinion; back them up with references or personal experience.
Use MathJax to format equations. MathJax reference.
To learn more, see our tips on writing great answers.
Some of your past answers have not been well-received, and you're in danger of being blocked from answering.
Please pay close attention to the following guidance:
- Please be sure to answer the question. Provide details and share your research!
But avoid …
- Asking for help, clarification, or responding to other answers.
- Making statements based on opinion; back them up with references or personal experience.
To learn more, see our tips on writing great answers.
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3061641%2fgenerating-function-of-numbers-of-visits-up-to-time-n%23new-answer', 'question_page');
}
);
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown